Nanostructure Based Sensors for Gas Sensing: from Devices to Systems - Donato, Nicola (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The development of solid state gas sensors based on microtransducers and nanostructured sensing materials is the key point in the design of portable measurement systems able to reach sensing and identification performance comparable with analytical ones. In such a context several efforts must be spent of course in the development of the sensing material, but also in the choice of the transducer mechanism and its structure, in the electrical characterization of the performance and in the design of suitable measurement setups. This call for papers invites researchers worldwide to report about their novel results on the most recent advances and overview in design and measurements for applications in gas sensors, along with their relevant features and technological aspects. Original research papers are welcome (but not limited) on all aspects that focus on the most recent advances in: (i) basic principles and modeling of gas and VOCs sensors; (ii) new gas sensor principles and technologies; (iii) Characterization and measurements methodologies; (iv) transduction and sampling systems; (vi) package optimization; (vi) gas sensor based systems and applications.